Thailand : Selected Issues. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Selected Issues paper analyzes factors that could bring inflation back to target in Thailand. The paper estimates a hybrid New Keynesian Phillips curve with time varying parameters to gauge the quantitative role of (long-term) inflation trends, economic slack, and import price inflation in shaping inflation dynamics. The analysis reveals some important changes in Thailand's inflation dynamics. It suggests that the impact of lower import prices was a major factor behind the decline in headline inflation in 2015, with low oil prices the largest contributor to inflation dynamics. Monetary policy easing, within a broader expansionary policy mix, should help bring inflation back to target.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet